KOMUNIKASI RITUAL BERBASIS MODERASI BERAGAMA DALAM RITUAL PERANG TOPAT DAN PUJAWALI PURA LINGSAR - Yuniati, Ketut (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relation, 2023)
This study aims to examine ritual communication based on religious moderation in the rituals of the Topat War and Pujawali at Lingsar Temple. Lingsar Village is a village located in West Lombok Regency and has a heterogeneous life with a majority population of Muslims and Hindus who both live side by side and in harmony. In the village of Lingsar there is a garden called Taman Lingsar which every year is the place where religious rituals take place, namely the Topat War by Muslims and Pujawali Pura Lingsar by Hindus. This research was designed in a qualitative descriptive form. The results of the study show that the Topat War in question is the throwing of topat/rhombus between Muslim and Hindu communities. In this ritual, there is an indicator of religious moderation, namely national commitment, the community carries out the ritual as a form of their commitment to the nation even though they have different cultural and religious ethnic groups, namely the Sasak tribe who are Muslim and the Balinese who are Hindu, but basically they are one unit of Indonesia. Next is tolerance, harmonization of the two ethnic groups, namely the Sasak tribe who are Muslim and the Balinese who are Hindu but still get along well and help each other to carry out the ritual process. The third indicator is anti-violence, even though this ritual is called Topat War but there is absolutely no element of violence, the people carry out the Topat War with great joy and enthusiasm, even before the ritual is carried out the community carries out mutual cooperation in preparing for the Topat War ritual process. The last indicator is accommodative to local culture by carrying out the Topat War and Pujawali Pura Lingsar as a form of cultural preservation.